PRP THERAPY SIGNIFICANTLY REDUCES URINARY INCONTINENCE SEVERITY AND IMPROVES QUALITY OF LIFE - Muzafarovna, Mukhammadzhonova Mohidil (Journal of Medical Genetics and Clinical Biology, 2024)
This study explores the efficacy of Platelet-Rich Plasma (PRP) therapy in treating urinary incontinence (UI) among women in Samarkand, Uzbekistan. Despite existing treatments, UI remains a significant concern, and PRP therapy's regenerative potential offers a promising alternative. Addressing a knowledge gap in long-term efficacy and quality of life impacts, a mixed-methods approach was employed, assessing 120 participants using ICIQ-SF, UDI-6, and SF-36 scores. Results indicated significant improvements in UI severity and overall quality of life, suggesting that PRP therapy could be a valuable, minimally invasive treatment. Further research is needed to optimize protocols and assess long-term outcomes